Digital Capability and Digital Innovation: The Impact of Small Business Sustainability During Pandemic Covid 19 - Yudha Prakasa (Universitas Batanghari, 2022)
This study aims to explain and analyze the effect of digital capabilities on digital capabilities and the sustainability of small businesses. This research is classified as explanatory research using a quantitative approach. This study involved 153 creative small businesses in Surabaya City with three leading sectors: fashion, culinary, and interior design. The sampling technique used proportional random sampling. The questionnaire was distributed using Google Forms. The study results show that Digital Capability has a significant effect on Digital Innovation; Digital Capability and Digital Innovation have also been directly proven to improve the Business Sustainability of small business owners during the Covid 19 pandemic. Digital Capability will increase the sustainability of small and large businesses if, at the same time, business owners also increase Digital Innovation in managing both the innovation process, organizational innovation management, and innovation in marketing. These three innovations can mediate and strengthen the influence of Digital Capability on SMEs' Business Sustainability.